Electrocatalytic Water Oxidation Promoted by 3 D Nanoarchitectured Turbostratic δ‐MnOx on Carbon Nanotubes. Issue 22 (20th July 2017) - Zhang, Biaobiao; Li, Yuanyuan; Valvo, Mario; Fan, Lizhou; Daniel, Quentin; Zhang, Peili; Wang, Linqin; Sun, Licheng
Abstract: The development of manganese‐based water oxidation electrocatalysts is desirable for the production of solar fuels, as manganese is earth‐abundant, inexpensive, non‐toxic, and has been employed by the Photosystem II in nature for a billion years. Herein, we directly constructed a 3 D nanoarchitectured turbostratic δ‐MnO x on carbon nanotube‐modified nickel foam (MnO x /CNT/NF) by electrodeposition and a subsequent annealing process. The MnO x /CNT/NF electrode gives a benchmark catalytic current density (10 mA cm −2 ) at an overpotential ( η ) of 270 mV under alkaline conditions. A steady current density of 19 mA cm −2 is obtained during electrolysis at 1.53 V for 1.0 h. To the best of our knowledge, this work represents the most efficient manganese‐oxide‐based water oxidation electrode and demonstrates that manganese oxides, as a structural and functional model of oxygen‐evolving complex (OEC) in Photosystem II, can also become comparable to those of most Ni‐ and Co‐based catalysts. Abstract : Turbo‐active sites : A 3 D nanoarchitectured turbostratic δ‐MnO x is directly constructed on carbon nanotube‐modified nickel foam (MnO x /CNT/NF). The MnO x /CNT/NF electrode exhibits excellent performance for electrochemical water oxidation, giving a benchmark catalytic current density (10 mA cm −2 ) at an overpotential of 270 mV under alkaline conditions.